2007
DOI: 10.1111/j.1467-8543.2007.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Then and Now: Disability Legislation and Employers' Practices in the UK

Abstract: Using a longitudinal research design, this article considers employers' human resource management practices in respect of disability equality: in 1995 under the Disabled Persons (Employment) Act and in 2003 under the Disability Discrimination Act. The article analyses whether there has been a change to employers' practices and whether or not this change is associated with increased employment of disabled persons. The findings show that proactive HR measures to encourage disabled employment, including positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
4
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 20 publications
0
40
4
2
Order By: Relevance
“…However, our results do indicate that they are much more prone to do so during recessions. Second, while the longitudinal data document clearly that women were more likely to lose jobs during nonrecessionary periods, consistent with other evidence from Europe (Jones et al, 2006;Kruse and Schur, 2003;Woodhams and Corby, 2007), we were unable to disaggregate different economic sectors that may account for these gendered patterns, such as the traditionally female service industries. Similarly, we are unable to ascertain why men with poor health have become more likely to lose work during the crisis but the most likely explanation is the differential impact of the crisis on sectors dominated by men, for example construction and manufacturing sectors.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, our results do indicate that they are much more prone to do so during recessions. Second, while the longitudinal data document clearly that women were more likely to lose jobs during nonrecessionary periods, consistent with other evidence from Europe (Jones et al, 2006;Kruse and Schur, 2003;Woodhams and Corby, 2007), we were unable to disaggregate different economic sectors that may account for these gendered patterns, such as the traditionally female service industries. Similarly, we are unable to ascertain why men with poor health have become more likely to lose work during the crisis but the most likely explanation is the differential impact of the crisis on sectors dominated by men, for example construction and manufacturing sectors.…”
Section: Discussionmentioning
confidence: 62%
“…Yet, others have suggested that these results were artefactual, since the Americans with Disabilities Act increased the numbers of persons designated as disabled (Jolls and Prescott, 2004;Kruse and Schur, 2003). Further studies that have investigated the longer-term effects find that anti-discrimination policies improved employment rates among disabled people although, in the UK, there is suggestive evidence that they have benefited men more than women (Jones et al, 2006;Kruse and Schur, 2003;Woodhams and Corby, 2007). These observations are thought to be a product of women's overrepresentation in precarious employment, including part-time work and the service sector.…”
Section: Introductionmentioning
confidence: 83%
“…In the UK, evidence on issues such as employer awareness of the DDA, perceptions of disability, prevalence of adjustments and disability-related practices has largely come from specialized surveys of employers (Simm et al, 2007;Woodhams and Corby, 2007). The approach used here, which deploys a large-scale matched employee-employer dataset in 1 Direct evidence relating to workplace accommodations is limited.…”
mentioning
confidence: 99%
“…More critically, a communicator's abilities require a mix of priorities arising from the organisation and their own ethnocentric perspective embedded through historical, political, social and cultural experiences to affect their ability to include (Woodhams & Corby, 2007). By proactively exploring inclusion in policy and process, communicators can compare outcomes with their publics and address deficiencies.…”
Section: Reviewing Perspectives That Challenge a Culture Of Inclusionmentioning
confidence: 99%
“…This methodology aimed to interpret the beliefs and lived experiences of multiple publics to isolate effective communication processes. The investigation used principles of constructionism as 'constructed reality' informed by historical, political, social and cultural experiences that affect inclusion (Woodhams & Corby, 2007, Weerakkody, 2015. It is limited by the communicators' ethnocentric perspective as informed by their experience.…”
Section: Analysing Inclusive Practicementioning
confidence: 99%